1994
DOI: 10.1111/j.1365-2044.1994.tb03529.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from pre‐operative sedation with clonidine—brain stem auditory evoked response

Abstract: SummaryIn a randomised double-blind study, 34 elderly patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Due to their ability to reduce IOP and dampen the sympathetic response, alpha 2 agonists find useful application in ophthalmic procedures. Clonidine [4][5][6] and dexmedetomidine also have these characteristics as alpha 2 agonists. Dexmedetomidine is extremely selective and specific for the alpha-2 adrenergic receptor, whereas clonidine acts on both the alpha-1 and alpha-2 adrenergic receptors.…”
Section: To Study Dexmedetomidine's Effect On Intraocular Pressure Af...mentioning
confidence: 99%
“…Due to their ability to reduce IOP and dampen the sympathetic response, alpha 2 agonists find useful application in ophthalmic procedures. Clonidine [4][5][6] and dexmedetomidine also have these characteristics as alpha 2 agonists. Dexmedetomidine is extremely selective and specific for the alpha-2 adrenergic receptor, whereas clonidine acts on both the alpha-1 and alpha-2 adrenergic receptors.…”
Section: To Study Dexmedetomidine's Effect On Intraocular Pressure Af...mentioning
confidence: 99%
“…In a recent study, Kumar et al [22] observed that preoperative sedation with oral clonidine (5 mg.kg À1 ) causes no significant increase in the interpeak latencies and APL of BAEP waves I-V on recovery from cataract extraction under regional block. In this study, in the diazepam (oral) group there was a significant increase in interpeak latencies and APL of waves I-V. A few other authors have also demonstrated significant changes in evoked potentials following the administration of diazepam [91,92].…”
Section: Influence Of Anaesthetic Drugs On Sepsmentioning
confidence: 99%
“…Brainstem auditory-evoked potentials (BAEP, Fig. 2) are recorded during procedures in the posterior cranial fossa [16][17][18][19][20][21], to assess recovery from pre-operative sedation in regional anaesthesia [22] and during chronic pain management [23]. Visual-evoked potentials (VEP, Fig.…”
Section: Evoked Potentialsmentioning
confidence: 99%